Chemistry of xanthorrhizol: synthesis of several bisabolane sesquiterpenoids from xanthorrhizol - Sirat, Hasnah; Ngai, Mun Hong; Jauri, Mohd. Haffiz (Elsevier, 2007)
Abstract—()-Xanthorrhizol (1) isolated from the rhizomes of Curcuma xanthorrhiza has been transformed to several bisabolanetype sesquiterpenoids, in a stereoselective manner. 10R- and 10S-10,11-dihydro-10,11-dihydroxyxanthorrhizols (2, 3), ()-curcuquinone (4), ()-curcuhydroquinone (5), helibisabonol A (7) and allylic alcohol 8 have been prepared from xanthorrhizol in optically active forms. All the routes involved a Sharpless AD to introduce the stereogenic centre at C-10. 2006 Elsevier Ltd. All rights reserved.